2001
DOI: 10.1038/sj.jhh.1001180
|View full text |Cite
|
Sign up to set email alerts
|

Dose response effect of cyclical medroxyprogesterone on blood pressure in postmenopausal women

Abstract: Objective: This study was designed to compare with placebo the dose-response effect of cyclical doses of the C21 progestogen, medroxyprogesterone acetate (MPA) on blood pressure (BP) when administered to normotensive postmenopausal women receiving a fixed mid-range daily dose of conjugated equine oestrogen (CEE). Materials and methods: Twenty normotensive postmenopausal women (median age 53 years) participated in the study which used a double-blind crossover design. There were four randomised treatment phases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…One cross-sectional study in normotensive postmenopausal women demonstrated higher ambulatory BP in women treated with a combination of transdermal estrogen and norethisterone than in women treated with estrogen alone [72]. However, prospective studies failed to confirm this finding and even suggested dose-dependent BP-lowering effects of androgenic progestins [73,74]. Similarly, natural progesterone has not been found to interfere with the BP-lowering effect of transdermal estrogen [31].…”
Section: Effects Of Estrogen On Blood Pressure In Postmenopausal Womenmentioning
confidence: 84%
“…One cross-sectional study in normotensive postmenopausal women demonstrated higher ambulatory BP in women treated with a combination of transdermal estrogen and norethisterone than in women treated with estrogen alone [72]. However, prospective studies failed to confirm this finding and even suggested dose-dependent BP-lowering effects of androgenic progestins [73,74]. Similarly, natural progesterone has not been found to interfere with the BP-lowering effect of transdermal estrogen [31].…”
Section: Effects Of Estrogen On Blood Pressure In Postmenopausal Womenmentioning
confidence: 84%
“…Similarly, medroxyprogesterone acetate (MPA) appears to have BP neutral or lowering effects. In a double-blind, crossover study of postmenopausal women assigned to CEE and placebo or increasing doses of MPA, there was a dosedependent decrease in ambulatory daytime diastolic and mean BPs for women assigned to the progestin compared with placebo (Harvey et al, 2001). In contrast, most studies of synthetic progestins for contraception or hormone therapy have revealed a BP-elevating effect.…”
Section: Progestin Effects On Blood Pressurementioning
confidence: 99%